2014
DOI: 10.2134/jeq2013.05.0172
|View full text |Cite
|
Sign up to set email alerts
|

Study of Cloud Water Samples Collected over Northern Poland

Abstract: The paper gives the results of the first studies on the chemistry of cloud water collected during 3 mo (Aug.-Oct. 2010) in the free atmosphere over the area to the south of the Tri-City (Gdansk-Sopot-Gdynia) conurbation on the Gulf of Gdansk, Poland. Taken from cumulus, stratus, and stratocumulus clouds by means of an aircraft-mounted collector, the water samples were analyzed for the following contaminants: anions (chlorides, fluorides, nitrates, sulfates, and phosphates), cations (lithium, sodium, potassium,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“…The pH value of fog water was often lower than rain water, and acid damage to vegetation by fog water (Waldman et al, 1982) can be considerable because plant leaves are immersed in fog for long periods of time (Waldman et al, 1982 Wrzesinsky et al, 2000;Adzuhata et al, 2001). As a result, the chemical characteristics of fog water at montane forests have been highlighted by researchers in several regions (Aleksic et al, 2009;Polkowska et al, 2014;Michna et al, 2015;Wang et al, 2015). Köhler et al (2015) reported that atmospheric water and element inputs increased with the rise of elevation in temperate mountain forests, attributable mainly to fog and cloud deposition.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…The pH value of fog water was often lower than rain water, and acid damage to vegetation by fog water (Waldman et al, 1982) can be considerable because plant leaves are immersed in fog for long periods of time (Waldman et al, 1982 Wrzesinsky et al, 2000;Adzuhata et al, 2001). As a result, the chemical characteristics of fog water at montane forests have been highlighted by researchers in several regions (Aleksic et al, 2009;Polkowska et al, 2014;Michna et al, 2015;Wang et al, 2015). Köhler et al (2015) reported that atmospheric water and element inputs increased with the rise of elevation in temperate mountain forests, attributable mainly to fog and cloud deposition.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…The majority of cloud water field studies have focused on composition and sources of gaseous and particulate material affecting clouds in regions such as Asia (Desyaterik et al, 2013;Ghauri et al, 2001;Li et al, 2017;X. H. Liu et al, 2012;Sun et al, 2010Sun et al, , 2015Watanabe et al, 2001), North America (Bator & Collett, 1997;Boone et al, 2015;Collett et al, 1994;Deininger & Saxena, 1997;Hayden et al, 2008;Hutchings et al, 2008;Leaitch et al, 1992;Malcolm et al, 2003;Munger et al, 1989a;Pratt et al, 2013;Rao & Collett, 1998;Weathers et al, 1988), Europe (Cini et al, 2002;Fomba et al, 2015;Lammel, 1995;Marinoni et al, 2004;Plessow et al, 2001;Polkowska et al, 2014;Sedlak et al, 1997;van Pinxteren et al, 2016;Wieprecht et al, 2005;Wilkinson et al, 1997), the Caribbean Islands (Gioda et al, 2008(Gioda et al, , 2009(Gioda et al, , 2013, and over marine areas (Benedict et al, Wet scavenging comprises two microphysical processes: (i) the activation of particles to form cloud droplets (termed nucleation scavenging) and (ii) the incorporation of particles and gases into existing droplets (particles enter droplets by impaction and diffusion, whereas gases are partitioned into droplets by diffusion). It is also convenient to classify wet scavenging on the macrophysical scale according to whether it occurs in or below clouds.…”
Section: Introductionmentioning
confidence: 99%
“…The majority of cloud water field studies have focused on composition and sources of gaseous and particulate material affecting clouds in regions such as Asia (Desyaterik et al, ; Ghauri et al, ; Li et al, ; X. H. Liu et al, ; Sun et al, , ; Watanabe et al, ), North America (Bator & Collett, ; Boone et al, ; Collett et al, ; Deininger & Saxena, ; Hayden et al, ; Hutchings et al, ; Leaitch et al, ; Malcolm et al, ; Munger et al, ; Pratt et al, ; Rao & Collett, ; Weathers et al, ), Europe (Cini et al, ; Fomba et al, ; Lammel, ; Marinoni et al, ; Plessow et al, ; Polkowska et al, ; Sedlak et al, ; van Pinxteren et al, ; Wieprecht et al, ; Wilkinson et al, ), the Caribbean Islands (Gioda et al, , , ), and over marine areas (Benedict et al, ; Crahan et al, ; Hegg et al, ; Prabhakar et al, ; Sorooshian, Wang, Coggon, et al, ; Sorooshian et al, ; Straub et al, ; Wang et al, ; Youn et al, ). Vertically resolved cloud water data are scarce and have focused on continental orographic clouds (Fowler et al, ; Kins et al, ) and cumulus clouds (Leaitch et al, ).…”
Section: Introductionmentioning
confidence: 99%